Digital Phase Locked-Loop With Wide Tuning Range And Dynamic Phase Shift - Rosle, Anafaezalena (2014)
For decades, Phase Lock Loop (PLL) has been widely used in numerous systems, such as telecommunications and digital design, where it plays significant role in improving overall system timing. Moving forward, with the latest revolution towards System-on-chip technology (SOC), the need of PLL in the form of Integrated Circuits has been growing tremendously. Core of this research is to design a PLL with wide tuning range and dynamic phase shift feature, which is implemented in the Integrated Circuits level. In line with fierce competition and fast-paced semiconductor industry, PLL design with above features are definitely most sought after, as it will tremendously reduce turn-around time, cost and effort for a project. Wide tuning range is achieved by introducing new Voltage Control Oscillator architecture, which will be able to provide wide tuning range without using very high KVCO. The new architecture proposed in this project is in differential input structure and consists of MOSFETs and capacitors; thus the area of implementation is small.Besides, extra feature which is proposed in this PLL is Dynamic Phase Shift feature. Dynamically tunable phase shift is important since the accuracy of the phase could be adjusted without having to reprogram the PLL, thus saving a lot of time. Dynamic Phase Shift feature is a new idea, which its design is implemented by using UP/DOWN counters, OR and AND gates. The complete design includes synchronous system design work such as state machine, diagram and truth table for system simplification. This proposed design achieved all specifications with wide-tuning range of 600MHz to 1300MHz is achieved with control voltage swing of 0.9V to 1.5V. Besides, the maximum static phase error measured in the simulation is 66ps, which is smaller than 200ps specification. Highest Period Jitter is 181ps while Cycle-to-Cycle Jitter is 55ps. Both types of jitter are within specification; lower than 300ps. Dynamic Phase Shift also successfully implemented where the UP/DN signal as the control to indicate either the phase is to be shifted up or down.